Respuestas
Respuesta dada por:
0
3(x-2x+4+3x+15)=-3x-6
3(x-2x+3x+4+15)=-3x-6
3(-x+3x+19)=-3x-6
3(2x+19)=-3x-6
6x+57=-3x-6
6x+3x=-6-57
9x=-63
X=-63/9
X=-7
3(-7-2(-7-2)+3(-7+5))=-3(-7+2)
3(-7-2x-9+3x-2)=-3x-5
3(-7+18-6)=15
3(11-6)=15
3x5=15
15=15
3(x-2x+3x+4+15)=-3x-6
3(-x+3x+19)=-3x-6
3(2x+19)=-3x-6
6x+57=-3x-6
6x+3x=-6-57
9x=-63
X=-63/9
X=-7
3(-7-2(-7-2)+3(-7+5))=-3(-7+2)
3(-7-2x-9+3x-2)=-3x-5
3(-7+18-6)=15
3(11-6)=15
3x5=15
15=15
nayelyelorreaga:
ecuaciones de primer grado
Preguntas similares
hace 6 años
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años